Florianópolis: urban space, public power and discipline (the 1910s and 1920s) (Tempo e Argumento, 2011)
This article aims to discuss improvements in the legal apparatus introduced in Santa Catarina and its capital, especially during the 1910s and 1920s. This apparatus had the aim of better organizing and controlling the mobility of vehicles - motorized and/or driven by animals – on roads between municipalities and on the streets of the urban perimeter of Florianopolis. We also analyze the perceptions expressed by local government agencies of efforts to provide sanitation within the urban boundary of the state capital. These disciplinary actions sought to adapt the space to the civilizing attitudes propagated by local elites, as observed in factions associated with Republican points of view, who aspired - at least in theory – to the material and moral progress of Brazilian society at that time.
Keywords: disciplining; social behaviors; municipality; sanitation; hygiene